2016
DOI: 10.1111/1475-6773.12480
|View full text |Cite
|
Sign up to set email alerts
|

Impact of State Public Health Spending on Disease Incidence in the United States from 1980 to 2009

Abstract: Our analysis indicates that there is evidence of a significant, negative relationship between a state's public health spending and the incidence of two VPDs, mumps and rubella, in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…Mays and Smith showed that local public health spending was linked to lower mortality ( Mays & Smith, 2011 ). Similarly, county non-hospital health spending was associated with reductions ranging from 6% to 12% in vaccine-preventable disease incidence ( Verma, Clark, Leider, & Bishai, 2017 ). Research on the impact of county spending choices has been slowed by gaps in data availability and data comparability on spending at the county level.…”
Section: Introductionmentioning
confidence: 99%
“…Mays and Smith showed that local public health spending was linked to lower mortality ( Mays & Smith, 2011 ). Similarly, county non-hospital health spending was associated with reductions ranging from 6% to 12% in vaccine-preventable disease incidence ( Verma, Clark, Leider, & Bishai, 2017 ). Research on the impact of county spending choices has been slowed by gaps in data availability and data comparability on spending at the county level.…”
Section: Introductionmentioning
confidence: 99%
“…We controlled for specific populations, communities, and LHD characteristics known to be associated with STD rates 1–6,8 . Sociodemographic characteristics included age (percentages of residents younger than 5 years and older than 65 years), percentage of Black residents, percentage of Hispanic residents, unemployment rate, median household income, the percentage of households with public assistance income, federal poverty rate, and percentage residents over age 24 with high school or more education 40…”
Section: Methodsmentioning
confidence: 99%
“…Compelling evidence exists that public spending on the prevention and control of sexually transmitted diseases (STDs) is a good investment. Several studies report that greater amounts of federal and state STD spending are associated with decreases in federal and state STD incidence rates 1–6 . The finding is important because STDs are the most common notifiable infectious disease in the United States, 7 and STDs may lead to serious health complications if untreated 8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Dominique [ 17 ] has pointed, the government plays an important role in improving social welfare, while fiscal expenditure is the key to public goods and services. Cutler and Miller [ 18 ] and Verma et al [ 19 ] also point that public-health expenditure reflects the government’s public health policy and it is a contributing factor in maintaining the national health. Therefore, many researchers have carried out a serious of studies on public-health expenditure in various countries, such as the United States [ 20 ], Canada [ 21 ], Spain [ 22 ], China [ 6 ], India [ 23 ], and the United Kingdom [ 24 ].…”
Section: Introductionmentioning
confidence: 99%